Excluded from school: Autistic students' experiences of school exclusion and subsequent re-integration into school. (November 2017) - Brede, Janina; Remington, Anna; Kenny, Lorcan; Warren, Katy; Pellicano, Elizabeth
Background and aims: All children have the right to receive an education and to be included in school. Yet young people on the autism spectrum, who are already vulnerable to poor health and social outcomes, are at increased risk of school exclusion. The current study sought to understand the key factors surrounding the school exclusion experiences of a group of autistic students with particularly complex needs, and their subsequent re-integration into education. Method: We interviewed nine intellectually able students (eight male, one female; M age = 13.3 years), all with a diagnosis of autism and the majority with a history of demand avoidant behaviour. We also interviewed their parents and teaching staff about the students' past and current school experiences. All students were currently being educated within an 'Inclusive Learning Hub', specially designed to re-integrate excluded, autistic students back into school, which was situated within a larger autism special school. Results: Young people and their parents gave overwhelmingly negative accounts of the students' previous school experiences. Children's perceived unmet needs, as well as inappropriate approaches by previous school staff in dealing with children's difficulties, were felt to cause decline in children's mental health and behaviour and, ultimately, led to their exclusion from school. Four key factors for successful reintegration into school were identified, including (i) making substantial adjustments to the physical environment, (ii) promoting strong staff–student relationships, (iii) understanding students' specific needs, and (iv) targeted efforts towards improving students' wellbeing. Conclusion: The culmination – and escalation – of challenges students experienced in the students' previous placements could suggest that the educational journey to exclusion from school is an inevitable consequence for at least some autistic children, including those with particularly complex behaviour, as sampled here. Yet, our study encouragingly showed that this was not necessarily the case. All the young people we spoke to reported being happy, safe and secure in their current placement, and re-engaged with school life. Outstanding issues remain, however, with regard to children's reportedly slow academic progress and difficulties generalising the positive behaviour shown in school across home and community contexts. Implications: More remains to be done to ensure that autistic children and young people's progress at school is also mirrored in other settings. Future research also needs to develop more preventative approaches to avoid exclusion from school, including efforts towards improving education professionals' knowledge and awareness of autism, and effective ways of responding to these students' needs.